Isolation, characterization, and application of lytic bacteriophages for controlling Enterobacter cloacae complex (ECC) in pasteurized milk and yogurt - Nasr-Eldin, Mohamed A; Gamal, Eman; Hazza, Mahmoud; Abo-Elmaaty, Sabah A (Folia microbiologica, 2023)
Reducing bacterial pathogen contamination not only improves overall global public health but also diminishes food waste and loss. The use of lytic bacteriophages (phages) that infect and kill bacteria could be a beneficial tool for suppressing bacterial growth during dairy products storage time. Four Enterobacter cloacae (E. cloacae) complex isolates which were previously isolated from contaminated dairy products were used to identify lytic phages in wastewater. Phages specific to multi-drug resistant (MDR) E. cloacae complex 6AS1 were isolated from local sewage. Two novel phages vB_EclM-EP1 and vB_EclM-EP2 were identified as myoviral particles and have double-stranded DNA genome. Their host range and lytic capabilities were detected using spot test and efficiency of plating (EOP) against several bacterial isolates. The phages had a latent period of 30 min, and a large burst size of about 100 and 142 PFU/cell for vB_EclM-EP1 and vB_EclM-EP2, respectively. Both phages were viable at pH ranging 5-9 and stable at 70 °C for 60 min. The individual phages and their cocktail preparations (vB_EclM-EP1 and vB_EclM-EP2) reduced and inhibited the growth of E. cloacae complex 6AS1 during challenge test in milk and yogurt samples. These results indicate that the E. cloacae complex-specific phages (vB_EclM-EP1 and vB_EclM-EP2) have a potential application as microbicidal agents in packaged milk and milk derivatives during storage time. In addition, our environment is a rich sources of lytic phages which have potential use in eliminating multidrug-resistant isolates in food industry as well as in biocontrol.
Keywords: jogurt; Milk; Refuse Disposal; mléko; Animals; bakteriofágy; Biocontrol; odpadky - odstraňování; zvířata; Bacteriophage; Bacteriophages; Yogurt; Enterobacter cloacae complex; Enterobacter cloacae